2007
DOI: 10.1016/j.neuron.2007.02.024
|View full text |Cite
|
Sign up to set email alerts
|

TRPM8 Is Required for Cold Sensation in Mice

Abstract: ThermoTRPs, a subset of the Transient Receptor Potential (TRP) family of cation channels, have been implicated in sensing temperature. TRPM8 and TRPA1 are both activated by cooling; however, it is unclear whether either ion channel is required for thermosensation in vivo. We show that mice lacking TRPM8 have severe behavioral deficits in response to cold stimuli. In thermotaxis assays of temperature gradient and two-temperature choice assays, TRPM8-deficient mice exhibit strikingly reduced avoidance of cold te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
812
3
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 801 publications
(874 citation statements)
references
References 35 publications
52
812
3
7
Order By: Relevance
“…Second, we found that mouse primary somatosensory forepaw cortex (S1) is necessary for thermal perception. Third, the TRPM8 cold receptor protein was necessary for mild cold temperature perception, suggesting that cold avoidance behaviors that are impaired in Trpm8 -/-mutant mice could be a result of a lack of fine temperature perception [4][5][6] . Finally, our primary sensory nerve recordings identified polymodal C fibers with low thresholds for cooling as the likely drivers for fine cooling perception in mice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, we found that mouse primary somatosensory forepaw cortex (S1) is necessary for thermal perception. Third, the TRPM8 cold receptor protein was necessary for mild cold temperature perception, suggesting that cold avoidance behaviors that are impaired in Trpm8 -/-mutant mice could be a result of a lack of fine temperature perception [4][5][6] . Finally, our primary sensory nerve recordings identified polymodal C fibers with low thresholds for cooling as the likely drivers for fine cooling perception in mice.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that the TRPM8 ion channel present in sensory afferents is an important transducer of cold [4][5][6]27 . We found that Trpm8 -/-12 mutant mice are incapable of perceiving mild cold and this lack of behavior is correlated with the loss of cold-evoked activity in cortical L2/3 neurons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations